2012
DOI: 10.5539/ijbm.v8n1p26
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Cultural Intelligence on Employee Job Performance: An Empirical Study on King Abdel-Aziz Hospital in Al-Taif Governorate, Kingdom of Saudi Arabia

Abstract: This research explores the impact of Cultural Intelligence (CQ) on Employee Job Performance (EJP). One of the intercultural effectiveness outcomes of CQ is task performance. CQ is an important factor in effective performance and interaction among various industries and environments. In other words, CQ is an important attribute for EJP because employees with high levels of CQ achieve high performance levels.This study was conducted at King Abdel-Aziz Hospital in Al-Taif Governorate (one of the most popular hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Task and contextual performance(Abdul Malek & Budhwar 2013;Ang et al 2007;Chen et al 2010;Chen et al 2011;Chen et al 2012;Duff et al 2012;Nafei 2013; Rockstuhl et al 2013a,b;Ş ahin et al 2013;Sri Ramalu et al 2012a;Wu & Ang 2011) n Leader performance in culturally diverse teams(Groves & Feyerherm 2011) n International leadership potential(Kim & Van Dyne 2012) n Cross-border leadership effectiveness(Rockstuhl et al 2011) …”
mentioning
confidence: 99%
“…Task and contextual performance(Abdul Malek & Budhwar 2013;Ang et al 2007;Chen et al 2010;Chen et al 2011;Chen et al 2012;Duff et al 2012;Nafei 2013; Rockstuhl et al 2013a,b;Ş ahin et al 2013;Sri Ramalu et al 2012a;Wu & Ang 2011) n Leader performance in culturally diverse teams(Groves & Feyerherm 2011) n International leadership potential(Kim & Van Dyne 2012) n Cross-border leadership effectiveness(Rockstuhl et al 2011) …”
mentioning
confidence: 99%
“…A general view of recent studies carried out on healthcare service organizations in the Kingdom of Saudi Arabia showed that researchers addressed concepts in these organizations such as lean methodology (Hassanain et al, 2017), self-management (Sabbah & Al-Shehri, 2014), organizational change (Nafei, 2014), nurses' job satisfaction (Al-Ahmadi, 2002;Alshmemri et al, 2016), cultural intelligence (Nafei, 2013), total quality management (Alaraki, 2014), employee empowerment (Sweis et al, 2013), quality of healthcare services (Algahtani et al, 2017), hospitals performance (Ahmad et al, 2013), employees work-life balance (Azeem & Altalhi, 2015), patient safety climate (Walston et al, 2010), sources of work stress among hospital staff (Al-Omar, 2003), burnout among healthcare providers (Bany-Hamdan et al, 2019), patient satisfaction (Ahmad et al, 2016), job design (Al-Maabadi et al, 2018), and employee motivation and job satisfaction in hospitals (Slimane, 2017). These are just examples of many works conducted on healthcare organizations in the Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…al., 2012;Nafei, 2013). In the descriptive study by Nafei (2013), total of 280 physicians, nurses, administrative staff, and auditors working in 600 bed hospital, two groups of employees (physicians and nurses vs. administrative staff and auditors) are compared in terms of cultural intelligence and employee job satisfaction. There are total of 165 physicians and nurses vs. 115 administrative staff and auditors.…”
Section: Introductionmentioning
confidence: 99%